Construction estimating industry standards - Shopware (Firm) (New Jersey : Shopware Productions, 2004)
In this program, students will learn a number of industry-standard techniques used to calculate the amounts of building materials for many common construction project
Title from title screen
Teacher's guide online on www.shopware.usa.com
DVD format
Keywords: House construction; House construction -- Estimates; Building trades